Effectiveness of Disinfectant Liquid Soaps in the Reduction of Candida spp Present in Complete Dentures: A Crossover Randomized Clinical Trial - Tasso, Camilla Olga [UNESP]; Zoccolotti, Jacqueline de Oliveira [UNESP]; Ferrisse, Tulio Morandim [UNESP]; Malavolta, Isadora Ferreira [UNESP]; Jorge, Janaina Habib [UNESP] (Quintessence Publishing Co Inc, 2020)
Purpose: To evaluate the effectiveness of liquid disinfectant soaps for the reduction of microorganisms present on maxillary complete dentures. Materials and Methods: The selected patients (N = 28) were randomly divided into four groups (n = 7), and each group underwent all four disinfection treatments in a different order. The disinfection treatments evaluated were: 0.5% sodium hypochlorite (positive control); Dettol liquid soap; Lifebuoy liquid soap; and phosphate-buffered saline solution (negative control). The patients were instructed to immerse their maxillary dentures in the disinfectant solution for 8 hours (overnight) for 7 days, with the solutions in a randomized sequence with a washout period of 1 week between solutions. Biofilm samples of the dental prostheses were obtained before and after each treatment with a sterile swab, and the microbiologic material was diluted and plated in selective media for Candida spp. Colony-forming unit count (CFU/mL) was performed in each group. One-way ANOVA with Welch correction was used for analysis, with Games-Howell post hoc test with a significance level of .05. Results: A 3-log reduction in microorganisms was considered effective compared to baseline. The highest incidence observed was for Candida albicans, which presented with a frequency between 66% and 92%, followed by C tropicalis, with a frequency between 7% and 33%, in all experimental groups. Sodium hypochlorite was able to reduce more than 3 log(10) of microorganisms for all patients, showing high antifungal effectiveness for both C albicans and C tropicalis species. Regarding the experimental groups, both liquid soaps (Dettol and Lifebuoy) were effective in reducing the two types of microorganisms. Conclusion: Liquid soaps were effective at reducing biofilm and may be an alternative for disinfection of removable partial dentures or complete dentures.